Can educational robotics introduce young children to robotics and how can we measure it?. (6th September 2018) - Castro, Emanuela; Cecchi, Francesca; Valente, Massimiliano; Buselli, Elisa; Salvini, Pericle; Dario, Paolo
Abstract: Studies have shown that educational robotics (ER) may impact student learning, especially in relation to STEM (science, technology, engineering, and mathematics) areas. In the STEM framework, particularly for younger children, the "E" and the "T" are considered to be missing letters, because few studies have concentrated on teaching and evaluating technology and engineering through ER activities. This study aimed to develop and test the efficacy of an ER protocol to teach robotics in a sample of 389 students, hypothesizing that girls would be as successful as boys. A Robotics Questionnaire assessing the basics of robotics was developed for this study. A Wilcoxon nonparametric test was performed in order to evaluate improvements ( p < 0.05). A Mann–Whitney nonparametric test was performed in order to test the presence of gender differences ( p < 0.05). Data indicated significant improvements for all the age ranges considered. No gender differences were found. In order to evaluate the efficacy of a didactic intervention utilizing ER, it is important to assess the impact on children's technological and engineering (robotics, in particular) knowledge. Lay Description: What is already known about this topic: Studies have shown that educational robotics (ER) has a potential impact on student learning. In the STEM framework, the "E" and the "T" are considered the STEM missing letters. What this paper adds: This study aims at developing and testing the efficacy of an ER protocol to teach robotics. The hypothesis that girls will be equally successful than boys is explored too, and no gender differences were found. Implications for practice and/or policy: Our results suggest that ER can be utilized to learn robotics, bringing technology in the schools. ER could be considered as a tool able to contribute to girl's involvement in STEM.